The influence of gender and wealth inequality on Alzheimer's disease among the elderly: A global study. Issue 4 (April 2023) - Yu, Shoukai; Qian, Lingmei; Ma, Jun
Abstract: This study was designed to explore the relationship between Alzheimer's disease (AD) rates and socioeconomic conditions in 120 countries. We used mixed effect models to investigate the relationship between the rates of AD and socioeconomic data. This study is among the first studies to put forward statistical evidence of a significant association between AD and other dementias among the elderly and socioeconomic inequality. These findings could help to inform the policies to be designed to improve the quality of interventions for AD.